Hubungan Peran Bidan, Dukungan Suami dan Akses Informasi dengan Kecemasan Menghadapi Persalinan Pada Ibu Hamil Usia Remaja - Indah Sri Wahyuni; Agnomelsya Bangaran; Yusmiyati Yusmiyati (Indonesian Journal of Midwifery Scientific, 2025)
Background: Pregnancy experienced by teenagers is the first experience, so the third trimester is felt to be more anxious because it is getting closer to the birthing process. Mothers will tend to feel anxious about their pregnancy, feel restless and afraid of childbirth. Objective: To determine the relationship between the role of midwives, husband's support, and access to information with the anxiety of teenage pregnant women facing childbirth in the work area of the Sukalarang Health Center in 2024. Methodology: This type of quantitative research with a cross sectional research design. The research sample was 40 third trimester pregnant women in their teens who visited ANC at the Johar Baru Community Health Center, taken using a simple random sampling technique. Data was obtained by distributing questionnaires. Univariate and bivariate data analysis using the chi-square test. Results: univariate analysis showed that 46 (53.5%) respondents experienced moderate anxiety during childbirth, 219 (55.4%) respondents had a good midwife role, and 54 (62.8%) had husband support. ) respondents, and good access to information was 49 (57.0%) respondents. There is a relationship between the role of midwives (p-value= 0.020 and Odds Ratio= 3.100), husband's support (p-value= 0.012 and Odds Ratio= 3.517), and access to information (p-value= 0.021 and Odds Ratio= 3.092) with HIV prevention /AIDS during the preconception period in the Sukalarang Health Center working area in 2024. Conclusions and Suggestions: There is a relationship between the role of midwives, husband's support, and access to information with the anxiety of teenage pregnant women in facing childbirth in the work area of the Sukalarang Health Center in 2024. It is hoped that husbands will always accompany their wives both before and after delivery, and fulfill all their needs pregnant women, provide more intense affection so that pregnant women do not feel anxious before giving birth.